2011
DOI: 10.1371/journal.pone.0027718
|View full text |Cite
|
Sign up to set email alerts
|

The Proteomics of Colorectal Cancer: Identification of a Protein Signature Associated with Prognosis

Abstract: Colorectal cancer is one of the commonest types of cancer and there is requirement for the identification of prognostic biomarkers. In this study protein expression profiles have been established for colorectal cancer and normal colonic mucosa by proteomics using a combination of two dimensional gel electrophoresis with fresh frozen sections of paired Dukes B colorectal cancer and normal colorectal mucosa (n = 28), gel image analysis and high performance liquid chromatography–tandem mass spectrometry. Hierarch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 48 publications
3
73
0
Order By: Relevance
“…A recent proteomics study showed that ALDH1 was down-regulated in lymph node metastasis of colon carcinoma cells [28]. Our experiments showed that ALDH1 is significantly up-regulated in colon cancer cells transfected with NGX6, suggesting that NGX6 may up-regulate ALDH1 expression to inhibit oncogenesis and metastasis.…”
Section: Discussionsupporting
confidence: 47%
“…A recent proteomics study showed that ALDH1 was down-regulated in lymph node metastasis of colon carcinoma cells [28]. Our experiments showed that ALDH1 is significantly up-regulated in colon cancer cells transfected with NGX6, suggesting that NGX6 may up-regulate ALDH1 expression to inhibit oncogenesis and metastasis.…”
Section: Discussionsupporting
confidence: 47%
“…Similar to normal tissue, LIMK2 expression was relatively high in low grade adenomas but markedly decreased in high grade adenomas with low or high levels of dysplasia (figure 3A). We next stained a well-characterised TMA comprised of 650 patient samples of normal intestines and tissue from Dukes A to Dukes C tumours, as well as representative lymph node metastases 21. By assigning staining intensity scores from 1 (low) to 6 (high), we established that median staining intensity in normal intestines scored 5 with relatively little variation (figure 3B,C).…”
Section: Resultsmentioning
confidence: 99%
“…However, the heterogeneity in the use of adjuvant treatment procedures makes it difficult to compare previously published findings to ours regarding this issue. After analyzing paired normal and tumor DNA, two studies found the differentially-expressed genes to be prognostic factors (Duncan et al, 2008;O'Dwyer et al, 2011). Our study focused on primary tumor DNAs and histo-clinical parameters.…”
Section: Discussionmentioning
confidence: 99%